Pembentukan Embrio Endospermik Sekunder Mangga (Mangifera indica L.) Gedong Gincu Klon 289 - Hindaningrum, Irni Furnawanthi; Wiendi, Ni Made Armini; Widodo, Winarso Drajad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTThe improvement of Mangifera indica L. by conventional breeding approaches has been confounded by the long generation cycle, low fruit set, single seed per fruit and high degree of cross pollination. Biotechnology complements conventional breeding and expedite the mango improvement programs. Endosperm culture is a direct method to produce triploid plants. This study aimed to obtain embryo from endosperm culture. The system of secondary somatic embriogenesis in mango described here represents a source of embryogenic material may be used for mass propagation and genetic manipulation of this crop. The method consisted of induction, proliferation, maturation, germination, and histological analysis of the obtaimed embryos. A protocol for plantlet regeneration was developed for Gedong Gincu mango clone 289 through secondary somatic embryogenesis. Primary somatic embryos (proembryo and cotyledonary embryos) were cultured in induction medium to induce the secondary somatic embryos. The best proliferation rate was 0.22 in medium with 1 g L-1 Poly Vinyl Pyrrolidone (PVP) for multiplication of secondary somatic embryos. Maturation of inoculum derived from the proliferation medium supplemented with 2 g L-1 of activated charcoal on medium containing 0.4 mg L-1 BAP provides the average 2.39 embryo formation of cotyledonari phase. The highest germination frequency (20%) was obtained in media with GA3 1.5 mg L-1.Keywords: endosperm, Gedong Gincu, Mangifera indica L, secondary endospermic embrio